Social Media Scandals: Audience Perception of Bangladeshi Film Celebrities and Industry Amidst The Surge of Hate Speech (Social Science Review, 2025)
Various pieces of evidence indicate that a scandal involving a film star’s personal life sets off a cascade of online attacks against that star. When people criticize or gossip about another person, they often paint an unfavorable picture of them. This research examines the growing phenomenon of social media scandals and hate speech targeted at film celebrities in Bangladesh. This research conducts a quantitative analysis involving 180 university students aged 18- 30, focusing on three primary aspects: the types of scandals and hate speech prevalent on social media, public comprehension of the lives of frequently scandalized celebrities, and the influence of scandals on perceptions of the film industry. The results indicate that marriage and relationship-related scandals constitute 65.4% of social media discourse, while relationship-based hate speech constitutes 75%. Pearson correlation (r) analysis indicates weak yet significant correlations between scandalized lives and perceptions of film quality (r = .210, p = .009) as well as industry image (r = .175, p = .030). Participants exhibit an understanding of the influence of scandals on celebrities’ personal lives (M = 3.69, SD = 0.92); however, this understanding has a negligible effect on their interest in films (M = 2.92, SD = 1.02). This indicates that audiences are capable of differentiating between personal controversies and their careers. The findings illustrate the intricate relationship among social media scandals, celebrity lives, and industry perception within Bangladesh’s film sector, emphasizing the need to improve online discourse and hate speech management.Social Science Review, Vol. 42(1), June 2025, pp. 147-162